Performance Feedback May Not Improve Radical Prostatectomy Outcomes: The Surgical Report Card (SuRep) Study. Issue 2 (10th August 2021) - Kumar, Ravi M.; Fergusson, Dean A.; Lavallée, Luke T.; Cagiannos, Ilias; Morash, Christopher; Horrigan, Michael; Mallick, Ranjeeta; Stacey, Dawn; Fung-Kee-Fung, Michael; Sands, David; Breau, Rodney H.
Abstract : Purpose: Oncologic, urinary, and sexual outcomes are important to patients receiving prostate cancer surgery. The objective of this study was to determine if providing surgical report cards (SuReps) to surgeons resulted in improved patient outcomes. Materials and Methods: A prospective before-and-after study was conducted at The Ottawa Hospital. A total of 422 consecutive patients undergoing radical prostatectomy were enrolled. The intervention was provision of report cards to surgeons. The control cohort was patients treated before report card feedback (pre-SuRep), and the intervention cohort was patients treated after report card feedback (post-SuRep). The primary outcomes were postoperative erectile function, urinary continence, and positive surgical margins. Results: Baseline characteristics were similar between groups. Almost all patients (99%) were continent and the majority (59%) were potent prior to surgery. Complete 1-year followup was available for 400 patients (95%). Nerve sparing surgery increased from 70% pre-SuRep to 82% post-SuRep (p=0.01). There was a nonstatistically significant increase in the proportion of patients with a positive surgical margin post-SuRep (31% pre-SuRep vs 39% post-SuRep, p=0.08). There was no difference in postoperative erectile function (17% vs 18%, p=0.7) and a decrease in continence (75% vs 65%, p=0.02) at 1 year postoperatively. Conclusions: The SuRep platform allows accurate reporting of surgical outcomes that can be used for patient counseling. However, the provision of surgical report cards did not improve functional or oncologic outcomes. Longer durations of feedback, report card modifications, or targeted interventions are likely necessary to improve outcomes.